Longitudinal analysis of peripheral immune cells in patients with multiple sclerosis treated with anti‐CD20 therapy - Mie Waede; Lasse F. Voss; Christina Kingo; Jesper B. Moeller; Maria L. Elkjaer; Zsolt Illes (Annals of Clinical and Translational Neurology)
Abstract Objective Anti‐CD20 therapy is a highly effective treatment for multiple sclerosis (MS). In this study, we investigated MS‐related changes in peripheral blood mononuclear cell (PBMC) subsets compared to healthy controls and longitudinal changes related to the treatment. Methods Multicolor spectral flow cytometry analysis was performed on 78 samples to characterize disease‐ and treatment‐related PBMC clusters. Blood samples from MS patients were collected at baseline and up to 8 months post‐treatment, with three collection points after treatment initiation. Unsupervised clustering tools and manual gating were applied to identify subclusters of interest and quantify changes. Results B cells were depleted from the periphery after anti‐CD20 treatment as expected, and we observed an isolated acute, transitory drop in the proportion of natural killer (NK) and NKT cells among the main populations of PBMC (P = 0.03, P = 0.004). Major affected PBMC subpopulations were cytotoxic immune cells (NK, NKT, and CD8+ T cells), and we observed a higher proportion of cytotoxic cells with reduced brain‐homing ability and a higher regulatory function as a long‐term anti‐CD20‐related effect. Additionally, anti‐CD20 therapy altered distributions of memory CD8+ T cells and reduced exhaustion markers in both CD4+ and CD8+ T cells. Interpretation The findings of this study elucidate phenotypic clusters of NK and CD8+ T cells, which have previously been underexplored in the context of anti‐CD20 therapy. Phenotypic modifications towards a more regulatory and controlled phenotype suggest that these subpopulations may play a critical and previously unrecognized role in mediating the therapeutic efficacy of anti‐CD20 treatments.